The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1073/pnas.1217321110
|View full text |Cite
|
Sign up to set email alerts
|

Cell-to-cell propagation of infectious cytosolic protein aggregates

Abstract: Prions are self-templating protein conformers that replicate by recruitment and conversion of homotypic proteins into growing protein aggregates. Originally identified as causative agents of transmissible spongiform encephalopathies, increasing evidence now suggests that prion-like phenomena are more common in nature than previously anticipated. In contrast to fungal prions that replicate in the cytoplasm, propagation of mammalian prions derived from the precursor protein PrP is confined to the cell membrane o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
101
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(102 citation statements)
references
References 49 publications
(63 reference statements)
1
101
0
Order By: Relevance
“…Pioneering studies with prion proteins (PrP) in lower eukaryotes (i.e. yeast and filamentous fungi) have revealed that they can act as 'epigenetic' elements and can account, at least in part, for non-Mendelian patterns of inheritance for several traits (Hofmann et al 2013). Mammalian prions share many common features with their counterparts in yeast, but their function and patterns of inheritance are less well known.…”
Section: Inter(trans)generational Inheritancementioning
confidence: 99%
“…Pioneering studies with prion proteins (PrP) in lower eukaryotes (i.e. yeast and filamentous fungi) have revealed that they can act as 'epigenetic' elements and can account, at least in part, for non-Mendelian patterns of inheritance for several traits (Hofmann et al 2013). Mammalian prions share many common features with their counterparts in yeast, but their function and patterns of inheritance are less well known.…”
Section: Inter(trans)generational Inheritancementioning
confidence: 99%
“…Recently, it has been demonstrated that several disease-associated aggregates, including human (1-3) and yeast prions (4), A␤ (5), Tau (6), ␣-synuclein (7), SOD1 (8), and PolyQ (9), can cross cellular membranes and spread aggregation from cell to cell (10). This has led to the notion that all of these proteins potentially possess a certain degree of prionoid behavior (8,11,12).…”
mentioning
confidence: 99%
“…Tethering to membranes and clustering in lipid raft domains may increase the effective local concentration of GPI-anchored Sup35NM such that a critical concentration for spontaneous aggregation can be reached, as has been reported previously (77). Such spontaneous aggregates have not been observed in systems where Sup35 is expressed in the cytosol (57,58), possibly because in this environment, where proteins are less restricted, the local critical concentration required for aggregation is not GPI were stained without permeabilization with anti-GFP primary antibody and secondary antibody conjugated to HRP, which catalyzes the conversion of DAB substrate into a product detectable by TEM. Staining was present all along the surface membranes of transfected cells, with occasional small regions of more intense staining in both GFP GPI and Sup35-GFP GPI -Sol cells (arrowheads).…”
Section: Discussionmentioning
confidence: 59%
“…Ure2p) form amyloid in the yeast cytosol (56). In previous studies, we and others reported that Sup35NM is able to propagate as a prion in mammalian cells (47,57,58) and that GPI anchoring facilitates aggregate propagation between N2a cells, resembling mammalian prion behavior (47). In the present work, we go on to characterize the ultrastructural and biochemical features of GPI-anchored Sup35NM aggregates.…”
mentioning
confidence: 99%